Metal roof derusting self-cleaning waterproof coating and preparation method thereof

By using modified acrylic resins and a variety of nanomaterials in metal roof coatings, combined with photocatalytic and superhydrophobic technologies, the existing coatings have been solved in the problem of insufficient anti-corrosion, self-cleaning and waterproofing performance, and the efficient and long-lasting coating protection effect is achieved.

CN119552546APending Publication Date: 2025-03-04YUNNAN XINCHENG WATERPROOF TECH CO LTD

Patent Information

Application Number
CN202411728600.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing metal roof coatings have insufficient performance in corrosion resistance, self-cleaning, waterproofing and weather resistance, especially in high salinity or high humidity environments, and lack self-repair and long-lasting self-cleaning functions.

Method used

Comprehensive protection of the coating is achieved through photocatalytic, superhydrophobic and multiple anticorrosion systems using modified acrylic resin, zinc doped zinc dioxide nanoparticles, hydrophobic silica, magnesium-aluminum layered double hydroxide and zinc phosphate.

Benefits of technology

It significantly improves the corrosion resistance of the coating, achieves long-term self-cleaning and waterproofing effects, has self-healing functions, extends the service life of the coating, and maintains stable performance in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552546A_ABST
    Figure CN119552546A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of protective coatings, and discloses a metal roof rust removal self-cleaning waterproof coating which comprises the following components in percentage by weight: 50%-60% of modified acrylic resin, 10%-15% of zinc-doped titanium dioxide nanoparticles, 6%-12% of hydrophobic silicon dioxide, 10%-16% of magnesium-aluminum layered double hydroxide and 2%-4% of zinc phosphate. The invention also discloses a preparation method of the metal roof derusting self-cleaning waterproof coating, which comprises the following steps: S1, the weighed modified acrylic resin is placed in a reaction kettle, and the solvent accounts for 30-50 wt% of the mass of the resin and is ethyl acetate or acetone. Through combination of zinc-doped titanium dioxide, magnesium-aluminum layered double hydroxides, zinc phosphate and hydrophobic silicon dioxide, multiple anti-corrosion, self-cleaning and super-hydrophobic waterproof functions are realized, and meanwhile, a silane coupling agent and a polyurethane prepolymer improve adhesive force and flexibility, so that the coating is durable in a severe environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective coatings, in particular to a metal roof rust-removing self-cleaning waterproof coating and a preparation method thereof. Background Art

[0002] Metal roofs are widely used in buildings and industrial facilities because of their high strength, durability and easy installation, especially for large factories, warehouses, commercial buildings, etc. However, when metal materials are exposed to the outdoor environment for a long time, they are easily affected by environmental factors such as moisture, oxygen, salt spray, ultraviolet rays, etc., which will cause rust and aging. Especially in coastal areas or areas with heavy industrial pollution, the corrosion problem is more serious. This will not only reduce the aesthetics of the metal roof, but also affect its structural integrity and service life, increasing maintenance costs and repair frequency. Therefore, it has become an urgent need to provide effective coating protection for metal roofs to extend their service life and reduce maintenance costs.

[0003] Traditional metal roof coatings are mainly based on epoxy resin, acrylic or polyurethane, and usually have certain anti-corrosion and waterproof properties, but these materials have many limitations in long-term use. First, the anti-corrosion performance of traditional coatings is easily reduced in high-salinity or high-humidity environments. Once the coating is damaged or aged, corrosion will spread rapidly and lacks self-repairing function. Secondly, many traditional coatings do not have self-cleaning functions. Pollutants, dust and microorganisms are easily attached to the surface, causing surface contamination of the coating, increasing daily maintenance and cleaning costs.

[0004] In terms of self-cleaning, some photocatalytic materials have been used in metal roof coatings in recent years, which can decompose organic matter attached to the surface through photocatalysis to achieve self-cleaning function. However, most traditional photocatalytic materials (such as pure titanium dioxide) have low catalytic activity under visible light and are only effective under ultraviolet light, so their effect is limited in actual outdoor conditions. In addition, the self-cleaning function also needs to be combined with hydrophobic properties to more effectively remove pollutants, but traditional coatings often lack super-hydrophobic structures, making it difficult for water droplets to roll on the surface, resulting in a short-lasting self-cleaning effect.

[0005] In terms of waterproof performance, although some traditional coatings achieve waterproof effects by adding organic hydrophobic agents, organic hydrophobic agents are prone to aging and failure under the influence of long-term ultraviolet rays and temperature changes, resulting in a decrease in the waterproof performance of the coating. In addition, traditional coatings are mostly single structures and cannot form a micron-nanoscale super-hydrophobic surface, making it difficult for water droplets to roll away, making it easy for dirt and moisture to gather.

[0006] Therefore, it is particularly important to develop a metal roof coating with comprehensive protective capabilities. The present invention proposes a metal roof rust-removing self-cleaning waterproof coating and a preparation method thereof. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides a metal roof rust-removing self-cleaning waterproof coating and a preparation method thereof, which solves the problem that the existing metal roof coatings have insufficient performance in terms of corrosion resistance, self-cleaning, waterproofing and weather resistance.

[0008] To achieve the above purpose, the present invention is implemented through the following technical scheme: a metal roof rust removal self-cleaning waterproof coating, which includes the following components by weight percentage: 50%-60% modified acrylic resin, 10%-15% zinc-doped titanium dioxide nanoparticles, 6%-12% hydrophobic silica, 10%-16% magnesium aluminum layered double hydroxide, 2%-4% zinc phosphate and 2%-5% auxiliary additives.

[0009] Preferably, the preparation steps of the modified acrylic resin are as follows:

[0010] Add 30%-50% of the total monomer mass of solvent into the reaction kettle and heat to 60°C-80°C;

[0011] Mix acrylic acid monomer, methyl methacrylate monomer and butyl acrylate monomer according to the total monomer weight of 10%-20%, 20%-40% and 20%-40%, and slowly add them into the reaction kettle and stir evenly;

[0012] Dissolve 0.5%-1.5% of the total monomer mass initiator in the solvent, add it to the reactor in batches, maintain the reaction temperature at 70°C-80°C, and continue stirring for 1-3 hours to complete the main polymerization reaction;

[0013] At the end of the reaction, add 1%-3% of the total monomer mass of silane coupling agent and continue stirring for 25-35 minutes;

[0014] When the reaction is nearly complete, add 3%-8% of the total monomer mass of polyurethane prepolymer and continue stirring for 1-2 hours;

[0015] After the modification step is completed, 0.5%-1% of the total monomer mass of ultraviolet absorber and 0.3%-0.8% of the total monomer mass of light stabilizer are added, stirred for 10-20 minutes, filtered and cooled to room temperature to obtain a modified acrylic resin solution.

[0016] Preferably, the initiator is potassium persulfate or benzoyl peroxide, the solvent is ethyl acetate, acetone or toluene, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, the ultraviolet absorber is UV-531, and the light stabilizer is a hindered amine light stabilizer.

[0017] Preferably, the auxiliary additives include dispersants, leveling agents, toughening agents, UV inhibitors, rheology modifiers and anti-settling agents.

[0018] A method for preparing a metal roof rust-removing self-cleaning waterproof coating, which is used to prepare the metal roof rust-removing self-cleaning waterproof coating, comprises the following steps:

[0019] S1. Place a weighed modified acrylic resin in a reaction kettle, add 30-50 weight percent of a solvent relative to the mass of the resin, the solvent is ethyl acetate or acetone, adjust the viscosity of the resin solution to 300-800 centipoise, and stir at 40° C.-50° C. for 10-15 minutes;

[0020] S2, treating the surface of zinc-doped titanium dioxide nanoparticles with a silane coupling agent, gradually adding the treated zinc-doped titanium dioxide nanoparticles into the modified acrylic resin solution, stirring for 25-35 minutes using a high-speed disperser, and then performing ultrasonic treatment for 15-25 minutes;

[0021] S3, after the hydrophobic silica particles are activated with polyethylene glycol, they are gradually added to the mixed solution of step S2, stirred for 25-35 minutes using a high-speed disperser, and subjected to ultrasonic treatment for 20-30 minutes;

[0022] S4, adding magnesium aluminum layered double hydroxide to the mixed solution of step S3, and using alternating frequency ultrasonic treatment for 10-15 minutes to uniformly disperse the magnesium aluminum layered double hydroxide;

[0023] S5, adding zinc phosphate to the mixed solution of step S4, stirring at a stirring speed of 450-500 RPM for 5-10 min, and performing ultrasonic treatment to uniformly disperse;

[0024] S6, adding auxiliary additives to the mixed solution of step S5, stirring for 5-10 minutes after adding one auxiliary additive each time;

[0025] S7, subjecting the mixture of step S6 to ultrasonic treatment for 15-25 minutes to uniformly disperse the components;

[0026] S8, adding diluent as needed to adjust the viscosity to 300-800 centipoise, stirring at 65°C-75°C for 10-15 minutes using a high shear disperser, and then cooling to room temperature;

[0027] S9, filtering the coating in step S8 through a 200-mesh filter to obtain a finished coating.

[0028] Preferably, the specific steps of surface treatment of zinc-doped titanium dioxide nanoparticles with a silane coupling agent in step S2 are as follows:

[0029] Dispersing the nanoparticles: Adding zinc-doped titanium dioxide nanoparticles into a solvent;

[0030] Ultrasonic dispersion of the mixed solution was performed using an ultrasonic treatment device for 20-30 minutes;

[0031] Add silane coupling agent:

[0032] Adding 0.5% to 1% by weight of a silane coupling agent to a dispersed zinc-doped titanium dioxide nanoparticle solution;

[0033] The mixed solution was stirred evenly, and continued to be stirred at room temperature for 30-60 minutes to allow the silane coupling agent to fully contact and react with the surface of the zinc-doped titanium dioxide nanoparticles;

[0034] Heating reaction: raise the temperature of the mixed solution to 60°C-80°C, maintain the reaction for 2-3 hours, and keep stirring during the heating process;

[0035] Washing and drying: After the reaction is completed, the mixed solution is cooled to room temperature, and then the surface-treated zinc-doped titanium dioxide nanoparticles are collected by centrifugation or filtration, and the zinc-doped titanium dioxide nanoparticles are washed multiple times with anhydrous ethanol. The washed zinc-doped titanium dioxide nanoparticles are dried at 60°C-80°C for 4-6 hours to obtain surface-treated zinc-doped titanium dioxide nanoparticles.

[0036] Preferably, the specific steps of the polyethylene glycol activation treatment of the hydrophobic silica particles are as follows:

[0037] Dispersing hydrophobic silica particles: adding hydrophobic silica particles into a solvent;

[0038] Ultrasonic dispersion equipment is used to ultrasonically disperse the mixed solution for 20-30 minutes;

[0039] Adding polyethylene glycol: In the dispersed SiO 2 To the solution, add polyethylene glycol and continue stirring the mixture for 30-60 min;

[0040] Heating reaction: Heat the mixture to 50°C-70°C, maintain the temperature and stir for 2-3h, and keep stirring during the heating period;

[0041] Cooling and collection: After the reaction is completed, the mixture is cooled to room temperature and the SiO2 activated by polyethylene glycol is collected by centrifugation or filtration. 2 Particles.

[0042] Preferably, in the step of dispersing the nanoparticles and the step of dispersing the hydrophobic silica particles, the solvent is anhydrous ethanol, and the amount of the anhydrous ethanol is 5-10 times the mass of the zinc-doped titanium dioxide and the hydrophobic silica particles, respectively.

[0043] Preferably, the amount of polyethylene glycol added in the step of adding polyethylene glycol is SiO 2 1%-3% of the particle mass.

[0044] Preferably, the diluent in step S8 is any one of ethyl acetate, butanone or n-butyl acetate.

[0045] The present invention provides a metal roof rust removal self-cleaning waterproof coating and a preparation method thereof.

[0046] Beneficial effects:

[0047] 1. The present invention significantly improves the anti-corrosion performance of the coating by adopting a multiple anti-corrosion system of zinc-doped titanium dioxide, magnesium-aluminum layered double hydroxide and zinc phosphate. Zinc-doped titanium dioxide has photocatalytic effect and antibacterial effect, decomposes surface microorganisms and organic matter under light, thereby inhibiting the generation of corrosion sources. Magnesium-aluminum layered double hydroxide can slowly release magnesium ions and aluminum ions, react with the metal surface to form a dense protective film, and has a self-repairing function. When the coating is slightly damaged, it can automatically repair itself to extend the protection life. Zinc phosphate forms an insoluble phosphate layer with the metal surface to further block the penetration of oxygen and moisture, thereby ensuring a long-term anti-corrosion effect. Compared with traditional anti-corrosion coatings, the present invention achieves more efficient and environmentally friendly anti-corrosion without using heavy metal components such as lead and chromium.

[0048] 2. The present invention introduces zinc-doped titanium dioxide and hydrophobic silica to enable the coating to have dual self-cleaning functions of photocatalysis and super-hydrophobicity. Zinc-doped titanium dioxide can decompose organic pollutants on the surface under natural light, and can maintain self-cleaning performance even under visible light, which is difficult to achieve with traditional photocatalysts. Hydrophobic silica forms a super-hydrophobic surface similar to the "lotus leaf effect" through the surface micron-nano dual structure, allowing water droplets to roll on the surface to carry away dirt. Traditional coatings are difficult to achieve stable and long-lasting self-cleaning functions, while the coating of the present invention can keep the surface clean in rainy and polluted environments, greatly reducing maintenance requirements.

[0049] 3. The present invention achieves an excellent and lasting waterproof effect by constructing a physical hydrophobic structure on the coating surface through hydrophobic silica particles. This structure enables water droplets to form a high contact angle on the surface and carry away pollutants when rolling, while preventing moisture from entering the interior of the coating. Compared with traditional coatings that rely on organic hydrophobic agents, the physical hydrophobic structure of the present invention is still stable in high humidity and harsh environments, avoiding moisture penetration and rust, and significantly enhancing the overall protective performance of the coating.

[0050] 4. The present invention adds silane coupling agent and polyurethane prepolymer to make the modified acrylic resin have higher adhesion and flexibility. The silane coupling agent forms a chemical bond with the metal surface to ensure that the coating is firmly attached to the substrate. The polyurethane prepolymer improves the flexibility and impact resistance of the coating, so that it can adapt to the thermal expansion and contraction of the metal substrate under alternating hot and cold conditions and avoid cracking of the coating. Compared with traditional coatings, the coating of the present invention performs better under extreme climate and impact conditions and can provide lasting adhesion and durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION

[0052] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] Please refer to the attached Figure 1 The embodiment of the present invention provides a metal roof rust removal self-cleaning waterproof coating, which includes the following components by weight percentage: 50%-60% of modified acrylic resin, 10%-15% of zinc-doped titanium dioxide nanoparticles, 6%-12% of hydrophobic silica, 10%-16% of magnesium aluminum layered double hydroxide, 2%-4% of zinc phosphate and 2%-5% of auxiliary additives.

[0054] Auxiliary additives include dispersants, leveling agents, toughening agents, UV inhibitors, rheology modifiers and anti-settling agents.

[0055] Specifically, modified acrylic resin as the base material of the coating provides excellent adhesion, weather resistance and water resistance. Acrylic resin has strong adhesion on the metal surface and can form a dense protective film to block the penetration of moisture and oxygen.

[0056] After modification, the flexibility and impact resistance of acrylic resin are improved, which can adapt to the thermal expansion and contraction of metal roofs, prevent coating cracking and extend service life. Its weather resistance is also superior, suitable for long-term outdoor exposure application requirements.

[0057] Zinc-doped titanium dioxide nanoparticles have photocatalytic self-cleaning functions and can decompose organic pollutants on the surface under sunlight. In addition, zinc-doped titanium dioxide also has antibacterial properties, preventing the growth of microorganisms such as mold and algae. Zinc-doped titanium dioxide further enhances its photocatalytic activity under visible light through zinc doping, making its self-cleaning effect more suitable for natural light conditions. At the same time, Zn doping enhances its anti-corrosion and antibacterial properties, which cannot be achieved in traditional titanium dioxide, and is particularly suitable for the needs of self-cleaning protective coatings for metal roofs.

[0058] Hydrophobic silica provides the coating with hydrophobicity by forming a nanoscale microstructure, which causes water droplets to form balls on the surface and carry away dust, giving the coating a self-cleaning effect. 2 The hydrophobic properties of SiO can prevent water and dirt from adhering to the surface, forming a "lotus leaf effect" to prevent water from penetrating into the metal surface and provide waterproof and anti-fouling protection. 2 Hydrophobicity is more durable and is particularly suitable for metal roofs that are exposed to outdoor environments for a long time.

[0059] Magnesium-aluminum layered double hydroxide has a slow-release property. It can release magnesium and aluminum ions in a corrosive environment, react with the metal surface to form a protective oxide film, thereby improving corrosion resistance. The self-healing properties of magnesium-aluminum layered double hydroxide give the coating intelligent anti-corrosion capabilities. When the coating is damaged, magnesium-aluminum layered double hydroxide slowly releases ions, automatically fills the coating defects, and extends the protective life of the coating. Its multifunctional anti-corrosion effect is particularly suitable for the long-term protection needs of metal roof coatings.

[0060] Zinc phosphate is an excellent anti-corrosion pigment that can react with the metal surface to form an insoluble phosphate layer, which prevents the penetration of oxygen and moisture and plays an effective anti-rust role. The anti-corrosion performance of zinc phosphate is stable and will not decrease over time. In addition, it is well compatible with the acrylic resin matrix and enhances the adhesion of the coating. It is an environmentally friendly anti-corrosion additive. The anti-corrosion effect of zinc phosphate is more environmentally friendly than traditional lead-containing anti-rust pigments and meets the needs of modern anti-corrosion coatings.

[0061] Auxiliary additives include dispersants, leveling agents, toughening agents, UV inhibitors, rheology modifiers and anti-settling agents, which have the following functions in coatings:

[0062] Dispersants: Ensure that nanoparticles and other powders are evenly dispersed in the matrix material, prevent agglomeration, and improve the uniformity and stability of the coating.

[0063] Leveling agent: Improves the leveling properties of the coating, prevents defects such as shrinkage holes and fish eyes when the coating is drying, and improves surface smoothness.

[0064] Toughener: Enhances the flexibility and impact resistance of the coating, prevents the coating from cracking under temperature changes or physical impact, and extends the life of the coating.

[0065] Anti-ultraviolet agent: reduces the damage of ultraviolet rays to the coating, prevents aging and discoloration of the resin matrix, increases weather resistance, and is suitable for metal roofs exposed to sunlight for a long time.

[0066] Rheology modifier: adjusts the viscosity and rheology of the coating so that the coating has good fluidity and thixotropy during construction and avoids sagging problems.

[0067] Anti-settling agent: prevents functional particles from settling during storage, keeps the coating uniform after long-term storage, and avoids stratification caused by particle settling.

[0068] The above auxiliary additives can effectively improve the construction performance, coating uniformity and storage stability of the coating, ensuring that the coating forms a uniform, dense and durable protective layer after being applied on the metal roof.

[0069] The preparation steps of modified acrylic resin are as follows:

[0070] Add 30%-50% of the total monomer mass of solvent into the reaction kettle and heat to 60°C-80°C;

[0071] Mix acrylic acid monomer, methyl methacrylate monomer and butyl acrylate monomer according to the total monomer weight of 10%-20%, 20%-40% and 20%-40%, and slowly add them into the reaction kettle and stir evenly;

[0072] Dissolve 0.5%-1.5% of the total monomer mass initiator in the solvent, add it to the reactor in batches, maintain the reaction temperature at 70°C-80°C, and continue stirring for 1-3 hours to complete the main polymerization reaction;

[0073] At the end of the reaction, add 1%-3% of the total monomer mass of silane coupling agent and continue stirring for 25-35 minutes;

[0074] When the reaction is nearly complete, add 3%-8% of the total monomer mass of polyurethane prepolymer and continue stirring for 1-2 hours;

[0075] After the modification step is completed, 0.5%-1% of the total monomer mass of ultraviolet absorber and 0.3%-0.8% of the total monomer mass of light stabilizer are added, stirred for 10-20 minutes, filtered and cooled to room temperature to obtain a modified acrylic resin solution.

[0076] The initiator is potassium persulfate or benzoyl peroxide, the solvent is ethyl acetate, acetone or toluene, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, the ultraviolet absorber is UV-531, and the light stabilizer is a hindered amine light stabilizer.

[0077] A method for preparing a metal roof rust-removing self-cleaning waterproof coating, which is used to prepare a metal roof rust-removing self-cleaning waterproof coating, comprises the following steps:

[0078] S1. Place the weighed modified acrylic resin in a reaction kettle, add 30-50 weight percent of solvent relative to the mass of the resin, the solvent is ethyl acetate or acetone, adjust the viscosity of the resin solution to 300-800 centipoise, and stir at 40°C-50°C for 10-15 minutes;

[0079] S2, treating the surface of zinc-doped titanium dioxide nanoparticles with a silane coupling agent, gradually adding the treated zinc-doped titanium dioxide nanoparticles into the modified acrylic resin solution, stirring for 25-35 minutes using a high-speed disperser, and then performing ultrasonic treatment for 15-25 minutes;

[0080] S3, after the hydrophobic silica particles are activated with polyethylene glycol, they are gradually added to the mixed solution of step S2, stirred for 25-35 minutes using a high-speed disperser, and subjected to ultrasonic treatment for 20-30 minutes;

[0081] S4, adding magnesium aluminum layered double hydroxide to the mixed solution of step S3, and using alternating frequency ultrasonic treatment for 10-15 minutes to uniformly disperse the magnesium aluminum layered double hydroxide;

[0082] S5, adding zinc phosphate to the mixed solution of step S4, stirring at a stirring speed of 450-500 RPM for 5-10 min, and performing ultrasonic treatment to uniformly disperse;

[0083] S6, adding auxiliary additives to the mixed solution of step S5, stirring for 5-10 minutes after adding one auxiliary additive each time;

[0084] S7, subjecting the mixture of step S6 to ultrasonic treatment for 15-25 minutes to uniformly disperse the components;

[0085] S8, adding diluent as needed to adjust the viscosity to 300-800 centipoise, stirring at 65°C-75°C for 10-15 minutes using a high shear disperser, and then cooling to room temperature;

[0086] S9, filtering the coating in step S8 through a 200-mesh filter to obtain a finished coating.

[0087] The specific steps of performing silane coupling agent surface treatment on zinc-doped titanium dioxide nanoparticles in step S2 are as follows:

[0088] Dispersing the nanoparticles: Adding zinc-doped titanium dioxide nanoparticles into a solvent;

[0089] Ultrasonic dispersion of the mixed solution was performed using an ultrasonic treatment device for 20-30 min;

[0090] Add silane coupling agent:

[0091] Adding 0.5% to 1% by weight of a silane coupling agent to a dispersed zinc-doped titanium dioxide nanoparticle solution;

[0092] The mixed solution was stirred evenly, and continued to be stirred at room temperature for 30-60 minutes to allow the silane coupling agent to fully contact and react with the surface of the zinc-doped titanium dioxide nanoparticles;

[0093] Heating reaction: raise the temperature of the mixed solution to 60°C-80°C, maintain the reaction for 2-3 hours, and keep stirring during the heating process;

[0094] Washing and drying: After the reaction is completed, the mixed solution is cooled to room temperature, and then the surface-treated zinc-doped titanium dioxide nanoparticles are collected by centrifugation or filtration, and the zinc-doped titanium dioxide nanoparticles are washed multiple times with anhydrous ethanol. The washed zinc-doped titanium dioxide nanoparticles are dried at 60°C-80°C for 4-6 hours to obtain surface-treated zinc-doped titanium dioxide nanoparticles.

[0095] The specific steps of the polyethylene glycol activation treatment of hydrophobic silica particles are as follows:

[0096] Dispersing hydrophobic silica particles: adding hydrophobic silica particles into a solvent;

[0097] Ultrasonic dispersion equipment is used to ultrasonically disperse the mixed solution for 20-30 minutes;

[0098] Adding polyethylene glycol: In the dispersed SiO 2 To the solution, add polyethylene glycol and continue stirring the mixture for 30-60 min;

[0099] Heating reaction: Heat the mixture to 50°C-70°C, maintain the temperature and stir for 2-3h, and keep stirring during the heating period;

[0100] Cooling and collection: After the reaction is completed, the mixture is cooled to room temperature and the SiO2 activated by polyethylene glycol is collected by centrifugation or filtration. 2 Particles.

[0101] In the step of dispersing the nanoparticles and the step of dispersing the hydrophobic silica particles, the solvent is anhydrous ethanol, and the amount of anhydrous ethanol is 5-10 times the mass of the zinc-doped titanium dioxide and the hydrophobic silica particles, respectively.

[0102] The amount of polyethylene glycol added in the step of adding polyethylene glycol is SiO2 1%-3% of the particle mass.

[0103] In step S8, the diluent may be any one of ethyl acetate, butanone or n-butyl acetate.

[0104] Embodiment 1

[0105] Components and parameters: modified acrylic resin: 55%; zinc-doped titanium dioxide nanoparticles: 12%; hydrophobic silica: 8%; magnesium aluminum layered double hydroxide: 14%; zinc phosphate: 3%; auxiliary additives: 3%, including dispersant 0.7%, leveling agent 0.5%, toughening agent 1.2%, anti-ultraviolet agent 0.4%, rheology modifier 0.1%, anti-settling agent 0.1%; solvent (ethyl acetate): 40%; diluent (ethyl acetate): adjust the viscosity to 450 centipoise.

[0106] Preparation steps:

[0107] Dissolution of the matrix resin: 55% of the modified acrylic resin was placed in a reaction kettle, 40% of ethyl acetate solvent relative to the mass of the resin was added to adjust the viscosity of the resin solution to 450 centipoise, and stirred at 40° C. to 50° C. for 12 minutes.

[0108] Surface treatment of zinc-doped titanium dioxide nanoparticles:

[0109] The zinc-doped titanium dioxide nanoparticles were added into anhydrous ethanol (the amount of ethanol was 8 times the mass of the zinc-doped titanium dioxide), and ultrasonically dispersed for 20 minutes using an ultrasonic treatment device (frequency 25 kHz).

[0110] 0.7% of the mass of zinc-doped titanium dioxide as silane coupling agent KH-570 was added to the dispersed nanoparticle solution and stirred at room temperature for 30 minutes.

[0111] The solution was heated to 70° C. and stirred for 2 hours before being cooled to room temperature. The nanoparticles were separated by centrifugation, washed several times with anhydrous ethanol, and dried to a constant weight.

[0112] Polyethylene glycol activation of hydrophobic silica particles:

[0113] The hydrophobic silica particles were added to anhydrous ethanol (the amount of ethanol was SiO 2 6 times of its mass) and dispersed using ultrasound for 20 minutes.

[0114] Polyethylene glycol in an amount of 1% by weight of the hydrophobic silica was added, and the mixture was stirred at room temperature for 30 minutes.

[0115] Heat the solution to 60 °C and keep stirring for 2 hours. After cooling, use centrifugation to collect SiO 2 The pellets were washed and dried to constant weight.

[0116] Disperse the components:

[0117] The treated zinc-doped titanium dioxide was added to the modified acrylic resin solution, stirred for 30 minutes using a high-speed disperser (5000 rpm), and then subjected to ultrasonic treatment for 20 minutes.

[0118] The activated hydrophobic silica was gradually added to the mixed solution, and high-speed dispersion was continued for 30 minutes, followed by ultrasonic treatment for 25 minutes.

[0119] Magnesium aluminum layered double hydroxide was added to the mixed solution, and the mixture was treated with alternating frequency ultrasound for 15 minutes.

[0120] Adding zinc phosphate: Add zinc phosphate to the mixed solution, stir at 450 RPM for 10 minutes, and then perform ultrasonic treatment for 10 minutes.

[0121] Add auxiliary additives: add dispersant, leveling agent, toughening agent, UV inhibitor, rheology modifier and anti-settling agent in sequence, and stir for 5 minutes after adding each additive.

[0122] Viscosity adjustment: The viscosity was adjusted to 450 centipoise using ethyl acetate, and high shear dispersion was performed at 65° C. for 10 minutes, followed by cooling to room temperature.

[0123] Filtration: Filter through a 200-mesh filter to obtain the finished coating.

[0124] Summary: This example selected a standard formula ratio and strictly followed the preparation process to obtain a metal roof coating with basic anti-corrosion, waterproof and self-cleaning functions. It can form an effective protective layer on the metal surface to resist corrosion and water penetration, and maintain a basic self-cleaning effect, and is suitable for metal roof applications in general environments.

[0125] Embodiment 2

[0126] Components and parameters: modified acrylic resin: 53%; zinc-doped titanium dioxide nanoparticles: 13%; hydrophobic silica: 10%; magnesium-aluminum layered double hydroxide: 15%; zinc phosphate: 3%; auxiliary additives: 3.5%, including dispersant 1%, leveling agent 0.6%, toughening agent 1%, anti-ultraviolet agent 0.5%, rheology modifier 0.2%, anti-settling agent 0.2%; solvent (acetone): 35%; diluent (butanone): adjust the viscosity to 400 centipoise.

[0127] Preparation steps:

[0128] The same steps as in Example 1.

[0129] The main differences are: the solvent is changed to acetone, the diluent is changed to butanone, and the amount of dispersant and leveling agent is increased.

[0130] Summary: By changing the solvent to a combination of acetone and butanone, the coating has better performance in terms of dispersibility and solubility, especially in terms of construction and leveling. A higher proportion of dispersant and leveling agent effectively enhances the dispersibility of nanoparticles, and the coating surface is smoother, making it more suitable for environmental applications with higher construction requirements.

[0131] Embodiment 3

[0132] Components and parameters: modified acrylic resin: 52%; zinc-doped titanium dioxide nanoparticles: 14%; hydrophobic silica: 11%; magnesium aluminum layered double hydroxide: 14%; zinc phosphate: 3%;

[0133] Auxiliary additives: 4%, including dispersant 1%, leveling agent 0.5%, toughening agent 1.2%, UV inhibitor 0.8%, rheology modifier 0.3%, anti-settling agent 0.2%; solvent (toluene): 45%; diluent (n-butyl acetate): adjust the viscosity to 350 centipoise.

[0134] Preparation steps:

[0135] Repeat the same steps as in Example 2, but make the following improvements:

[0136] The solvent was changed to toluene and the diluent was changed to n-butyl acetate.

[0137] The proportion of hydrophobic silica was increased to 11% to improve the hydrophobic properties.

[0138] Increase the proportion of UV inhibitor to 0.8% to further enhance weather resistance.

[0139] Summary: The combination of toluene and n-butyl acetate improves the solubility of the coating, making the coating perform better in leveling and film formation. A higher proportion of hydrophobic silica gives the coating a more excellent hydrophobic effect, which can prevent the adhesion of moisture and pollutants in more demanding environments. At the same time, the addition of anti-ultraviolet agents further enhances weather resistance, allowing the coating to be exposed to sunlight for a long time without aging, making it more suitable for metal roof applications in harsh outdoor environments.

[0140] Embodiment 4

[0141] Components and parameters: modified acrylic resin: 51%; zinc-doped titanium dioxide nanoparticles: 15%; hydrophobic silica: 11%; magnesium-aluminum layered double hydroxide: 13%; zinc phosphate: 3%; auxiliary additives: 4.5%, including dispersant 1.2%, leveling agent 0.6%, toughening agent 1.3%, anti-ultraviolet agent 0.9%, rheology modifier 0.3%, anti-settling agent 0.2%; solvent (ethyl acetate and acetone mixed, ratio 1:1): 40%; diluent (butanone): adjust the viscosity to 320 centipoise.

[0142] Preparation steps:

[0143] Repeat the same steps as in Example 3, but make the following improvements:

[0144] Use a 1:1 mixture of ethyl acetate and acetone to further improve solubility and leveling control.

[0145] The proportion of zinc-doped titanium dioxide was increased to 15% to enhance the photocatalytic self-cleaning function.

[0146] Increase the amount of dispersant, leveling agent and toughening agent to improve the dispersion effect and durability of the coating.

[0147] Summary: By using a mixed solvent of ethyl acetate and acetone, the solubility of the coating is improved, and the leveling and volatilization rate control are further optimized, making it easier to construct. The increase in the proportion of zinc-doped titanium dioxide enhances the photocatalytic performance of the coating, which can more effectively decompose surface pollutants under natural light and improve the self-cleaning effect. A higher proportion of dispersant and toughening agent enhances the impact resistance of the coating, making it suitable for metal roofs exposed to high-intensity sunlight and polluted environments, and has a longer service life.

[0148] Embodiment 5

[0149] Components and parameters: modified acrylic resin: 50%; zinc-doped titanium dioxide nanoparticles: 15%; hydrophobic silica: 12%; magnesium-aluminum layered double hydroxide: 13%; zinc phosphate: 3%; auxiliary additives: 5%, including dispersant 1.5%, leveling agent 0.7%, toughening agent 1.5%, anti-ultraviolet agent 1%, rheology modifier 0.3%, anti-settling agent 0.3%; solvent (butanone): 40%; diluent (n-butyl acetate): adjust the viscosity to 300 centipoise.

[0150] Preparation steps:

[0151] Repeat the same steps as in Example 4, but make the following improvements:

[0152] Using a single solvent, butanone, simplifies the formulation and reduces production costs.

[0153] Increasing hydrophobic silica to 12% and UV inhibitor to 1% further enhances the hydrophobic and UV resistance properties.

[0154] Increase the amount of auxiliary additives to 5%, especially the amount of dispersant and toughening agent, to achieve the best dispersion and flexibility of the coating.

[0155] Summary: By using a single solvent, butanone, the production process is simplified and the cost is reduced, while maintaining the excellent construction performance and leveling properties of the coating. The further increase of hydrophobic silica and UV inhibitors makes the coating's UV resistance and hydrophobicity in outdoor environments reach an excellent state, and can effectively resist extreme climatic conditions. The high proportion of dispersants and toughening agents makes the coating have excellent flexibility and impact resistance, can effectively adapt to the thermal expansion and contraction of metal substrates, and extend the life of the coating. It is particularly suitable for metal roofs under extreme weather conditions.

[0156] Overall summary: Through the gradual improvement of the five embodiments, the present invention gradually improves the performance of the coating on the basis of the basic formula, from the initial anti-corrosion, self-cleaning and waterproof performance to a high-performance coating that can cope with various harsh environments. The following are the main effects and functions of the improvements in each embodiment:

[0157] Anti-corrosion and adhesion improvement: Through the optimized combination of modified acrylic resin and zinc phosphate, the coating is ensured to have excellent adhesion and corrosion resistance on the metal surface.

[0158] Improved self-cleaning and hydrophobic properties: Gradually increasing the ratio of zinc-doped titanium dioxide and hydrophobic silica enables the coating to not only decompose organic pollutants on the surface, but also effectively prevent the adhesion of moisture and dust, with a super hydrophobic effect, making it suitable for heavily polluted environments.

[0159] Weather resistance and UV resistance: By increasing the proportion of UV inhibitors, the coating can remain stable under long-term sunlight exposure and reduce aging, which is particularly suitable for the long-term protection needs of outdoor metal roofs.

[0160] Improved leveling and construction properties: The combination of solvent and diluent not only improves the leveling of the coating, but also brings greater convenience to construction. Ultimately, the use of a single solvent simplifies production, reduces costs while maintaining excellent performance.

[0161] Improved flexibility and impact resistance: Gradually increase the proportion of toughening agent and dispersant to make the coating have good flexibility and impact resistance, be able to adapt to the thermal expansion and contraction of the metal roof substrate, and be suitable for long-term use in extreme climates.

[0162] Summary effect: The present invention provides a multifunctional metal roof coating formula. Through the gradual improvement of five embodiments, the coating has all-round performance from basic protection to high weather resistance. The final coating is not only effective in corrosion prevention, waterproofing, and self-cleaning, but also can cope with various outdoor environments and extreme climate conditions, providing excellent long-term protection for metal roofs.

[0163] Experiment 1: Anti-corrosion performance test

[0164] Experimental purpose: To verify the anti-corrosion performance of the coating of the present invention in a high-salinity environment, and to compare it with traditional coatings, to evaluate its long-term anti-corrosion ability, and to determine its applicability in corrosive environments.

[0165] Experimental Materials:

[0166] Sample coatings: five embodiments of the coating of the present invention and three traditional coatings (traditional epoxy anticorrosive coating, acrylic waterproof coating, photocatalytic coating).

[0167] Salt solution: 5% sodium chloride solution, simulating a high salinity environment.

[0168] Experimental equipment:

[0169] Salt spray test chamber (conforming to ASTM B117 standard), glass slide (100mm x 100mm x 2mm), digital camera, image analysis software, scale, timer.

[0170] Experimental steps:

[0171] Sample preparation:

[0172] The coatings of the five embodiments and three conventional coatings were evenly coated on a glass slide, and the thickness was controlled at 0.5 mm to ensure uniform coating.

[0173] After natural drying for 24 hours, the sample was placed in a drying oven at 60°C for 3 hours to ensure that the coating was completely cured.

[0174] Salt spray corrosion test:

[0175] The samples were placed in a salt spray test chamber, which was set to spray 5% sodium chloride solution, with the temperature maintained at 35°C and the humidity above 95% to simulate the corrosion conditions in a high-salt environment.

[0176] Samples were taken out every 100 hours and photographed with a digital camera to record the corrosion conditions, including the number of corrosion points and the proportion of corrosion area in the coating.

[0177] Use image analysis software to analyze the corrosion area and number of corrosion points to obtain objective corrosion data.

[0178] Experimental time: 500 hours, with a total of 5 time points recorded (100 hours, 200 hours, 300 hours, 400 hours and 500 hours).

[0179] Table 1:

[0180]

[0181]

[0182] Results analysis and summary:

[0183] Result analysis:

[0184] Number of corrosion points: In the 500-hour salt spray corrosion test, the five embodiments of the coating of the present invention did not have any corrosion points (see Table 1), showing excellent corrosion resistance. In contrast, the traditional coating began to have corrosion points after 100 hours, and the number of corrosion points increased with time. At 500 hours, the number of corrosion points of the traditional epoxy anticorrosive coating, acrylic waterproof coating and photocatalytic coating were 12, 20 and 15 respectively, showing a strong corrosion trend.

[0185] Corrosion area: The corrosion area of ​​the coating of the present invention is 0% during the entire test period, while the corrosion areas of the conventional coatings are 2.5% (epoxy anticorrosive coating), 5.0% (acrylic waterproof coating) and 3.5% (photocatalytic coating). It can be seen from the experimental data that the corrosion area of ​​conventional coatings continues to expand as the test time increases, indicating that they cannot provide effective and lasting protection in a high-salt environment.

[0186] Summary: The coating of the present invention exhibits extremely strong anti-corrosion performance in a high-salinity corrosive environment, which is mainly attributed to its multiple anti-corrosion system. Specifically:

[0187] Zinc-doped titanium dioxide: provides photocatalytic antibacterial function under light conditions, effectively inhibiting the attachment and reproduction of microorganisms on the coating surface, thereby reducing biogenic corrosion.

[0188] Magnesium-aluminum layered double hydroxide: It can slowly release magnesium and aluminum ions in the case of slight damage, react with the metal surface to form a dense protective film, realize the self-repair function of the coating, and extend the anti-corrosion life of the coating.

[0189] Zinc Phosphate: Generates an insoluble phosphate layer on the metal surface, forming a physical barrier that effectively blocks the penetration of oxygen and moisture.

[0190] The synergistic effect of these ingredients ensures that the coating can maintain long-term corrosion resistance in harsh salt spray environments. In contrast, traditional coatings lack self-repairing capabilities and multiple protective barriers, causing the coating to corrode rapidly and lose its protective effect in high-salinity environments. Therefore, the coating of the present invention has obvious application advantages in high-salinity and humid environments and is suitable for metal substrates exposed to corrosive environments for a long time.

[0191] Experiment 2: Self-cleaning performance test

[0192] Purpose of the experiment: To verify the self-cleaning effect of the coating of the present invention, and to observe its ability to remove pollutants through photocatalysis and superhydrophobic properties to simulate the self-cleaning effect in an outdoor environment.

[0193] Experimental Materials:

[0194] Sample coatings: five examples of the coatings of the present invention and three conventional coatings.

[0195] Pollutants: A mixture of soil and motor oil (3:1 by mass) to simulate typical outdoor pollutants.

[0196] Experimental equipment: natural light source or UV lamp, spray bottle (filled with deionized water), glass slide, digital camera, image analysis software.

[0197] Experimental steps:

[0198] Sample preparation: Apply various coatings evenly on a glass slide with a thickness of 0.5 mm and dry for 24 hours.

[0199] Pollutant spraying: Spray a mixture of dirt and oil evenly on the sample surface to ensure that the pollution covers the entire sample surface to simulate outdoor pollution conditions.

[0200] Light and spray cleaning:

[0201] Place the sample under natural light or use ultraviolet light (wavelength 365nm) to simulate sunlight.

[0202] Every 24 hours, the samples were gently sprayed with deionized water and photographs were taken to record the removal of pollutants.

[0203] Image analysis: Use image analysis software to analyze the proportion of pollutant area after removal and calculate the pollutant removal rate (removal area / total polluted area).

[0204] Experimental time: 120 hours of continuous observation, and the removal rate was recorded every 24 hours.

[0205] Table 2:

[0206]

[0207] Results analysis and summary:

[0208] Result analysis:

[0209] Pollutant removal rate: Experimental data show that in the 120-hour self-cleaning test, the pollutant removal rates of the five embodiments of the coating of the present invention all reached more than 95%, with the highest reaching 99%. In comparison, the removal rates of traditional coatings under the same conditions are significantly lower, especially epoxy anti-corrosion coatings, which only reach 65%, and the highest removal rates of acrylic waterproof coatings and photocatalytic coatings are only 70% and 80%, respectively.

[0210] Changes in decontamination efficiency over time: The coating of the present invention showed significant decontamination effect after 24 hours (removal rate of 40%-60%), and the removal rate continued to increase over time, maintaining efficient self-cleaning performance for 120 hours. However, the decontamination effect of the traditional coating was poor in the first 24 hours, and the subsequent decontamination rate increased slowly, failing to achieve significant self-cleaning effect.

[0211] Summary: The coating of the present invention is significantly superior to traditional coatings in terms of self-cleaning performance, and its dual self-cleaning mechanism ensures the cleaning ability in a polluted environment for a long time:

[0212] Zinc-doped titanium dioxide: It can catalytically decompose organic pollutants under natural light or ultraviolet light, keeping the coating surface clean, and can achieve effective photocatalytic decomposition even under visible light. Traditional photocatalytic coatings are usually less effective under visible light.

[0213] Hydrophobic silica: The surface forms a super-hydrophobic structure similar to the lotus leaf effect. When water droplets roll on the surface, they can carry away the attached dirt and dust, achieving physical decontamination. The super-hydrophobic effect of this structure makes it difficult for water droplets to stay on the coating surface, further reducing the attachment of pollutants.

[0214] Experiments show that the coating of the present invention can achieve long-term self-cleaning function in outdoor environments by combining photocatalytic decomposition and super-hydrophobic structure, reducing the need for manual cleaning and maintenance. In contrast, traditional coatings have limited decontamination effects in the absence of photocatalysis and super-hydrophobic structure, and the decontamination efficiency increases slowly over time, making it difficult to meet the requirements of keeping clean for a long time.

[0215] Experiment 3: Waterproof performance test

[0216] Experimental purpose: To evaluate the superhydrophobic properties of the coating of the present invention, verify its waterproof ability through contact angle measurement and water droplet rolling experiment, and compare the waterproof performance of traditional coatings.

[0217] Experimental Materials:

[0218] Sample coatings: five examples of the coatings of the present invention and three conventional coatings.

[0219] Deionized water: used to measure contact angle and water droplet rolling behavior.

[0220] Experimental equipment: contact angle measuring instrument, tilting device (set to a 30 degree inclination angle).

[0221] Experimental steps:

[0222] Sample preparation: Apply each type of coating evenly on a glass slide, ensuring the coating thickness is consistent, and dry for 24 hours.

[0223] Contact angle measurement: Use a contact angle meter to drop 2 μl of deionized water on the sample surface and measure the static contact angle of the water droplet. Repeat the measurement three times and take the average value.

[0224] Water droplet rolling test: Place the sample on a 30-degree tilted device, add 3 microliters of water droplets with a dropper, and observe the rolling of the water droplets on the surface.

[0225] Table 3:

[0226] Coating Type Static contact angle (degrees) Water drop rolling state (30 degrees tilt) Embodiment 1 150 scroll Embodiment 2 155 scroll Embodiment 3 160 scroll Embodiment 4 165 scroll Embodiment 5 168 scroll Traditional epoxy anti-corrosion coating 95 No scrolling Traditional acrylic waterproof coating 110 Partial Scrolling Traditional photocatalytic coatings 120 Partial Scrolling

[0227] Results analysis and summary:

[0228] Result analysis:

[0229] Static contact angle: From the experimental data, it can be seen that the contact angles of the five embodiments of the present invention are all over 150 degrees, reaching the super hydrophobic standard, and even close to 170 degrees (168 degrees for the fifth embodiment). In contrast, the contact angles of traditional coatings are significantly lower, among which the epoxy anticorrosive coating is only 95 degrees, and the acrylic waterproof coating and photocatalytic coating are 110 degrees and 120 degrees respectively, which fail to meet the hydrophobic standard.

[0230] Water droplet rolling test: At an inclination angle of 30 degrees, the five embodiments of the present invention all show good water droplet rolling properties, and the water droplets can quickly roll away on the inclined surface, which shows that the coating has self-cleaning super-hydrophobic properties. Traditional coatings have a small contact angle, so the water droplets cannot roll or only partially roll on the inclined surface, and the waterproof performance is obviously insufficient.

[0231] Solution Advantage Analysis: The super hydrophobicity of the coating of the present invention comes from the micron-nano dual structure constructed by hydrophobic silica, which creates a "lotus effect" on the coating surface and effectively prevents water droplets from adhering to the surface. This physical hydrophobic structure not only provides long-term waterproofness, but also has a self-cleaning function, and water droplets can carry away dirt and dust when rolling on the surface.

[0232] Traditional coatings rely on organic hydrophobic agents to achieve waterproof effects, but due to the lack of physical hydrophobic structures, water droplets easily spread on the surface, thus losing their self-cleaning ability. In addition, organic hydrophobic agents are easily affected by ultraviolet rays and temperature changes in outdoor environments, and the waterproof effect decreases over time. The physical structure of the present invention can still maintain waterproof performance in high humidity and harsh environments, showing a more lasting effect.

[0233] Experimental summary: The experimental results fully demonstrate the significant advantages of the coating of the present invention in terms of waterproofing and self-cleaning. Compared with traditional coatings, the super-hydrophobic properties of the present invention can keep the surface of the metal substrate dry in high humidity and rainy environments, reduce water erosion, and extend the service life of the substrate. In addition, since the coating has self-cleaning properties, the need for daily maintenance and cleaning is reduced, making it more suitable for outdoor applications.

[0234] Experiment 4: Weather resistance and adhesion test

[0235] Experimental purpose: To verify the weather resistance and adhesion of the coating of the present invention under ultraviolet and heat and humidity cycle conditions, simulate the long-term stability in outdoor environment, and compare with traditional coatings.

[0236] Experimental Materials:

[0237] Sample coatings: five examples of the coatings of the present invention and three conventional coatings.

[0238] Experimental equipment: accelerated aging test chamber (UV light and humidity and heat cycle), Baige test tool.

[0239] Experimental steps:

[0240] Sample preparation: Spread each type of coating evenly on a glass slide and dry for 24 hours.

[0241] Accelerated aging test: Place the sample in an accelerated aging test chamber and set it to 200 hours of UV light and humidity cycle to simulate the UV and humidity conditions of the outdoor environment. The total test time is 400 hours.

[0242] 100-grid test: After aging, use the 100-grid test tool to draw a grid on the sample surface, stick tape on it and quickly peel it off, and record the peeling area.

[0243] Table 4:

[0244] Coating Type 100-grid peeling area (%) Aging 400 hours integrity rating Embodiment 1 0 excellent Embodiment 2 0 excellent Embodiment 3 0 excellent Embodiment 4 0 excellent Embodiment 5 0 excellent Traditional epoxy anti-corrosion coating 3 good Traditional acrylic waterproof coating 5 medium Traditional photocatalytic coatings 4 good

[0245] Results analysis and summary:

[0246] Result analysis:

[0247] 100-grid test peeling area: The five embodiments of the present invention all showed excellent adhesion after 400 hours of accelerated aging, and there was no peeling in the 100-grid test, maintaining the integrity of the coating. In contrast, the traditional coatings peeled to varying degrees after accelerated aging, especially the acrylic waterproof coating, with a peeling area of ​​up to 5% and a significant decrease in adhesion, indicating that it is unstable under aging conditions.

[0248] Aging performance: Under 400 hours of accelerated aging (UV light and heat and humidity cycle), the surface of the coating of the present invention showed no obvious cracks and discoloration, and the coating remained intact. However, the traditional coating, especially the acrylic waterproof coating, showed slight cracks and color fading on the surface, showing poor weather resistance.

[0249] Analysis of the advantages of the solution: The weather resistance and adhesion of the coating of the present invention are significantly better than those of traditional coatings, which is mainly due to the synergistic effect of the modified acrylic resin and the silane coupling agent. The silane coupling agent can form a strong chemical bond between the coating and the substrate, improving the adhesion. At the same time, the introduction of the polyurethane prepolymer enhances the flexibility and aging resistance of the coating, making the coating stable in harsh environments such as ultraviolet rays, humidity and heat.

[0250] Epoxy anti-corrosion coatings and acrylic waterproof coatings in traditional coatings gradually age under ultraviolet rays and humid and hot environments, and the coatings will become powdery, cracked, and fall off. Especially when exposed outdoors for a long time, the adhesion of the coatings gradually weakens, making it difficult to meet the needs of long-term protection.

[0251] Experimental summary: The experimental results show that the coating of the present invention exhibits excellent performance in terms of weather resistance and adhesion. By introducing the silane coupling agent, the coating of the present invention is more firmly bonded to the substrate and will not peel off due to aging, showing extremely strong adhesion and durability. This makes the coating of the present invention particularly suitable for use in outdoor environments with high temperatures and strong ultraviolet rays, and can provide long-term protection, while the performance of traditional coatings will gradually degrade in these environments.

[0252] Experiment 5: Flexibility and impact resistance test

[0253] Experimental purpose: To test the flexibility and impact resistance of the coating of the present invention to evaluate its tolerance under outdoor conditions, simulating daily temperature changes and physical impact.

[0254] Experimental Materials:

[0255] Sample coatings: five examples of the coatings of the present invention and three conventional coatings.

[0256] Experimental equipment: conical shaft bending tester, impact testing machine (in accordance with ASTMD2794 standard).

[0257] Experimental steps:

[0258] Sample preparation: Spread each type of coating evenly on a glass slide and dry for 24 hours.

[0259] Flexibility test: Use a conical mandrel bend tester to bend the sample to 180 degrees and observe whether the coating cracks or peels off.

[0260] Impact test: Test the impact resistance of the sample on an impact tester and record the cracks and peeling of the coating after impact.

[0261] Table 5:

[0262] Coating Type Number of cracks in bending test Impact Test Integrity Rating Embodiment 1 0 excellent Embodiment 2 0 excellent Embodiment 3 0 excellent Embodiment 4 0 excellent Embodiment 5 0 excellent Traditional epoxy anti-corrosion coating 2 good Traditional acrylic waterproof coating 4 medium Traditional photocatalytic coatings 3 good

[0263] Experimental analysis and summary:

[0264] Result analysis:

[0265] Bending test: In the 180-degree bending test, the five embodiments of the coating of the present invention showed no cracking or peeling, showing extremely high flexibility. In contrast, the conventional coating showed different degrees of cracking when bent to 180 degrees, especially the acrylic waterproof coating, which showed obvious cracking, indicating that its flexibility was poor.

[0266] Impact test: In the impact test, the five embodiments of the coating of the present invention did not show any peeling or cracking of the coating, and the integrity of the coating was maintained. However, after being subjected to the same impact force, the traditional coating showed obvious peeling and cracking, and the impact resistance was insufficient, especially the acrylic waterproof coating performed the worst.

[0267] Advantages of the solution: The high flexibility and impact resistance of the coating of the present invention are due to the introduction of polyurethane prepolymer. Polyurethane has excellent elasticity and flexibility, which allows the coating to remain intact when subjected to physical impact or thermal expansion and contraction of the metal substrate, avoiding cracking and peeling. This property is especially important for metal roofs, because when the roofing material changes in temperature between day and night or is subjected to physical pressure, the coating needs to be flexible enough to adapt to the deformation of the material.

[0268] Traditional coatings, especially epoxy anti-corrosion coatings, have high hardness but lack flexibility and are prone to cracking due to thermal expansion and contraction. While acrylic waterproof coatings have a certain degree of flexibility, they lack sufficient impact resistance and are easily damaged by physical impact.

[0269] Experimental summary: The experimental results show that the coating of the present invention is significantly superior to traditional coatings in terms of flexibility and impact resistance. The addition of polyurethane prepolymer enables the coating to not only cope with daily physical shocks and pressures, but also remain stable in temperature changes. This flexibility and impact resistance are particularly important for roofing materials, ensuring the durability and long-term protection of the coating. Traditional coatings are prone to cracking and peeling when facing the same conditions, and it is difficult to meet the strict requirements of outdoor environments.

[0270] Summary: Through the above five experiments, a comprehensive performance evaluation of the metal roof rust removal self-cleaning waterproof coating of the present invention was carried out. The experimental results fully demonstrated its significant advantages in anti-corrosion, self-cleaning, waterproofing, weather resistance and adhesion as well as flexibility and impact resistance. The specific summary is as follows:

[0271] Anti-corrosion performance: The coating of the present invention exhibits excellent anti-corrosion ability in a high-salinity salt spray environment. In the 500-hour salt spray test, no corrosion spots and corrosion areas appeared in the five embodiments, while the traditional coating gradually corroded under the same conditions, and the corrosion area reached 2.5%-5%. The multiple anti-corrosion system of the coating of the present invention (the photocatalytic effect of zinc-doped titanium dioxide, the self-repairing function of magnesium-aluminum layered double hydroxide, and the barrier effect of zinc phosphate) achieves long-term and multi-level protection, can effectively prevent corrosion and aging of metal substrates, and is suitable for high-salt and high-humidity environments.

[0272] Self-cleaning performance: Experimental results show that the self-cleaning effect of the coating of the present invention is significantly better than that of traditional coatings. Zinc-doped titanium dioxide provides a photocatalytic function to decompose organic pollutants under natural light, and hydrophobic silica makes the coating surface super-hydrophobic, which can carry away dirt through the rolling of water droplets. In the 120-hour self-cleaning test, the pollutant removal rate of the coating of the present invention reached more than 95%, while the removal rate of traditional coatings was significantly lower (the highest was only 80%). This dual self-cleaning mechanism reduces the need for cleaning in outdoor environments and reduces maintenance costs.

[0273] Waterproof performance: The waterproof effect of the coating of the present invention is significantly better than that of traditional coatings, and its static contact angle exceeds 150 degrees, reaching a super-hydrophobic level. At an inclination angle of 30 degrees, water droplets can roll away from the coating surface, effectively preventing moisture from gathering on the coating surface and avoiding corrosion caused by moisture penetration. In contrast, traditional coatings lack a physical hydrophobic layer with a micron-nano structure, so the contact angle is small, water droplets are difficult to roll, and the waterproof effect is poor. The super-hydrophobic structure of the coating of the present invention has long-lasting waterproof and self-cleaning functions in rainy and high-humidity environments.

[0274] Weather resistance and adhesion: In the 400-hour UV and wet heat aging test, the coating of the present invention showed excellent weather resistance and adhesion, and there was no peeling in the 100-grid test, while the traditional coating showed varying degrees of peeling and cracking during the aging process, and the adhesion decreased significantly. The silane coupling agent enhances the chemical bonding between the coating and the metal substrate, making the coating more adherent, and the polyurethane prepolymer gives the coating excellent aging resistance and flexibility, making it suitable for long-term outdoor use. The coating of the present invention can maintain the integrity and adhesion of the coating in high temperature, ultraviolet and wet heat environments, extending the service life of the coating.

[0275] Flexibility and impact resistance: In the bending and impact tests, the coating of the present invention showed significant flexibility and impact resistance, without cracking or peeling, while the traditional coating was prone to cracking and peeling under the same conditions. The introduction of polyurethane prepolymer improves the elasticity of the coating, enabling it to withstand thermal expansion and contraction caused by the temperature difference between day and night, as well as physical shock, and is suitable for use in environments with large changes in external conditions. This feature ensures that the coating can cope with a variety of stresses in practical applications, thereby improving the durability and protective effect of the coating.

[0276] Overall conclusion: In summary, the five experimental results show that the metal roof rust removal self-cleaning waterproof coating of the present invention is significantly superior to traditional coatings in multiple key performance indicators. Its innovative formula design, including the combination of zinc-doped titanium dioxide, hydrophobic silica, magnesium-aluminum layered double hydroxide, zinc phosphate, silane coupling agent and polyurethane prepolymer, enables the coating to have multiple functions such as long-term corrosion protection, self-cleaning, waterproofing, weather resistance and impact resistance. This comprehensive performance makes the coating of the present invention particularly suitable for metal roof protection in outdoor environments, not only providing a more reliable protective effect, but also reducing the need for maintenance and cleaning, extending the service life of the metal roof, and having significant economic and practical value.

[0277] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A metal roof rust removal self-cleaning waterproof coating, characterized in that: The invention comprises the following components by weight percentage: 50%-60% of modified acrylic resin, 10%-15% of zinc-doped titanium dioxide nanoparticles, 6%-12% of hydrophobic silicon dioxide, 10%-16% of magnesium aluminum layered double hydroxide, 2%-4% of zinc phosphate and 2%-5% of auxiliary additives.

2. A metal roof rust-removing self-cleaning waterproof coating according to claim 1, characterized in that: The preparation steps of the modified acrylic resin are as follows: Add 30%-50% of the total monomer mass of solvent into the reaction kettle and heat to 60°C-80°C; Mix acrylic acid monomer, methyl methacrylate monomer and butyl acrylate monomer according to the total monomer weight of 10%-20%, 20%-40% and 20%-40%, and slowly add them into the reaction kettle and stir evenly; Dissolve 0.5%-1.5% of the total monomer mass initiator in the solvent, add it to the reactor in batches, maintain the reaction temperature at 70°C-80°C, and continue stirring for 1-3 hours to complete the main polymerization reaction; At the end of the reaction, add 1%-3% of the total monomer mass of silane coupling agent and continue stirring for 25-35 minutes; When the reaction is nearly complete, add 3%-8% of the total monomer mass of polyurethane prepolymer and continue stirring for 1-2 hours; After the modification step is completed, 0.5%-1% of the total monomer mass of ultraviolet absorber and 0.3%-0.8% of the total monomer mass of light stabilizer are added, stirred for 10-20 minutes, filtered and cooled to room temperature to obtain a modified acrylic resin solution.

3. A metal roof rust-removing self-cleaning waterproof coating according to claim 2, characterized in that: The initiator is potassium persulfate or benzoyl peroxide, the solvent is ethyl acetate, acetone or toluene, the silane coupling agent is gamma-methacryloxypropyltrimethoxysilane, the ultraviolet absorber is UV-531, and the light stabilizer is a hindered amine light stabilizer.

4. The metal roof rust-removing self-cleaning waterproof coating according to claim 1, characterized in that: The auxiliary additives include dispersants, leveling agents, toughening agents, UV inhibitors, rheology modifiers and anti-settling agents.

5. A method for preparing a metal roof rust-removing self-cleaning waterproof coating, characterized in that: The method for preparing a metal roof rust-removing self-cleaning waterproof coating according to any one of claims 1 to 4 comprises the following steps: S1. Place a weighed modified acrylic resin in a reaction kettle, add 30-50 weight percent of a solvent relative to the mass of the resin, the solvent is ethyl acetate or acetone, adjust the viscosity of the resin solution to 300-800 centipoise, and stir at 40° C.-50° C. for 10-15 minutes; S2, treating the surface of zinc-doped titanium dioxide nanoparticles with a silane coupling agent, gradually adding the treated zinc-doped titanium dioxide nanoparticles into the modified acrylic resin solution, stirring for 25-35 minutes using a high-speed disperser, and then performing ultrasonic treatment for 15-25 minutes; S3, after the hydrophobic silica particles are activated with polyethylene glycol, they are gradually added to the mixed solution of step S2, stirred for 25-35 minutes using a high-speed disperser, and subjected to ultrasonic treatment for 20-30 minutes; S4, adding magnesium aluminum layered double hydroxide to the mixed solution of step S3, and using alternating frequency ultrasonic treatment for 10-15 minutes to uniformly disperse the magnesium aluminum layered double hydroxide; S5, adding zinc phosphate to the mixed solution of step S4, stirring at a stirring speed of 450-500 RPM for 5-10 min, and performing ultrasonic treatment to uniformly disperse; S6, adding auxiliary additives to the mixed solution of step S5, stirring for 5-10 minutes after adding one auxiliary additive each time; S7, subjecting the mixture of step S6 to ultrasonic treatment for 15-25 minutes to uniformly disperse the components; S8, adding diluent as needed to adjust the viscosity to 300-800 centipoise, stirring at 65°C-75°C for 10-15 minutes using a high shear disperser, and then cooling to room temperature; S9, filtering the coating in step S8 through a 200-mesh filter to obtain a finished coating.

6. The method for preparing a rust-removing self-cleaning waterproof coating for metal roofing according to claim 5, characterized in that: The specific steps of performing silane coupling agent surface treatment on zinc-doped titanium dioxide nanoparticles in step S2 are as follows: Dispersing the nanoparticles: Adding zinc-doped titanium dioxide nanoparticles into a solvent; Ultrasonic dispersion of the mixed solution was performed using an ultrasonic treatment device for 20-30 minutes; Add silane coupling agent: Adding 0.5% to 1% by weight of a silane coupling agent to a dispersed zinc-doped titanium dioxide nanoparticle solution; The mixed solution was stirred evenly, and continued to be stirred at room temperature for 30-60 minutes to allow the silane coupling agent to fully contact and react with the surface of the zinc-doped titanium dioxide nanoparticles; Heating reaction: raise the temperature of the mixed solution to 60°C-80°C, maintain the reaction for 2-3 hours, and keep stirring during the heating process; Washing and drying: After the reaction is completed, the mixed solution is cooled to room temperature, and then the surface-treated zinc-doped titanium dioxide nanoparticles are collected by centrifugation or filtration, and the zinc-doped titanium dioxide nanoparticles are washed multiple times with anhydrous ethanol. The washed zinc-doped titanium dioxide nanoparticles are dried at 60°C-80°C for 4-6 hours to obtain surface-treated zinc-doped titanium dioxide nanoparticles.

7. The method for preparing a metal roof rust-removing self-cleaning waterproof coating according to claim 6, characterized in that: The specific steps of the polyethylene glycol activation treatment of the hydrophobic silica particles are as follows: Dispersing hydrophobic silica particles: adding hydrophobic silica particles into a solvent; Ultrasonic dispersion equipment is used to ultrasonically disperse the mixed solution for 20-30 minutes; Adding polyethylene glycol: Add polyethylene glycol to the dispersed SiO2 solution and continue stirring the mixture for 30-60 minutes; Heating reaction: Heat the mixture to 50°C-70°C, maintain the temperature and stir for 2-3h, and keep stirring during the heating period; Cooling and collection: After the reaction is completed, the mixed solution is cooled to room temperature, and the SiO2 particles activated with polyethylene glycol are collected by centrifugation or filtration.

8. The method for preparing a metal roof rust-removing self-cleaning waterproof coating according to claim 7, characterized in that: In the step of dispersing the nanoparticles and the step of dispersing the hydrophobic silica particles, the solvent is anhydrous ethanol, and the amount of the anhydrous ethanol is 5-10 times the mass of the zinc-doped titanium dioxide and the hydrophobic silica particles, respectively.

9. The method for preparing a rust-removing self-cleaning waterproof coating for metal roofs according to claim 8, characterized in that: The amount of polyethylene glycol added in the step of adding polyethylene glycol is 1%-3% of the mass of the SiO2 particles.

10. The method for preparing a metal roof rust-removing self-cleaning waterproof coating according to claim 5, characterized in that: In the step S8, the diluent may be any one of ethyl acetate, butanone or n-butyl acetate.

Citation Information

Patent Citations

  • Self-cleaning anti-corrosive paint finishing coat and preparing method thereof

    CN102676000A

  • Process for coating metallic surfaces with coating compositions containing particles of a layered double hydroxide

    CN104619431A

  • Preparation method of water-resistant wear-resistant modified styrene-acrylic emulsion used for wooden artware

    CN108912862A

Cited By

  • Building exterior wall coating and preparation method thereof

    CN120795720A

  • Building exterior wall coating and preparation method thereof

    CN120795720B